Paper patching in traumatic perforation of tympanic membrane - Shinde, Vinod; Choudhary, Sudeep; Ingale, Mayur; Chavan, Paresh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Traumatic perforations are not new for ENT surgeons. The dictum for treatment is to keep the ear dry and leave the tympanic membrane to heal by itself. Most of the time it heals completely, but if it does not, a tympanoplasty is required. Methods: 144 patients of traumatic tympanic membrane perforation, who reported in the outdoor patient department of Otorhinolaryngology, at Dr. D. Y. Patil Medical college, DPU, Pune, were divided in two random groups; Group A was treated with standard treatment while Group B was treated with patching of perforation as an adjuvant to standard treatment. A simple paper, (from the envelop of gel foam) was used for this procedure. The standard taught and performed treatment for a tympanic membrane perforation is administering antibiotics, antihistaminic and anti-inflammatory drugs and keeping the ear dry; leaving the perforation for spontaneous healing. Results: Group A 75% perforations had healed while in Group B 97.22% perforations healed completely. Conclusions: Paper patching supports the healing tympanic membrane and significantly improves the chances of spontaneous healing thus reducing the requirement of surgical intervention.